Diffusion of hydrophobin proteins in solution and interactions with a graphite surface - Mereghetti, Paolo; Wade, Rebecca C. (BMC Biophysics, 2011)
Hydrophobins are small proteins produced by filamentous fungi that have a variety of biological functions including coating of spores and surface adhesion. To accomplish these functions, they rely on unique interface-binding properties. Using atomic-detail implicit solvent rigid-body Brownian dynamics simulations, we studied the diffusion of HFBI, a class II hydrophobin from Trichoderma reesei, in aqueous solution in the presence and absence of a graphite surface.